Reactive hyperaemia in the forearm skin of highly trained windsurfers - Heylen, E.; Simon, B.; Guerrero, F.; Elkaïm, J. -P.; Saïag, B.; Mansourati, J. (International Journal of Sports Medicine, 2005)
We undertook this study to determine whether long-term high intensity exercise would modify cutaneous endothelial-dependent vasodilation. We compared a group of 9 highly trained windsurfers (mean age: 24.5 ± 1.6 years) to a control group of 8 sedentary individuals (22.9 ± 0.4 years, NS). Laser Doppler was used to measure cutaneous blood flow in the resting state (baseline), during post-occlusive hyperaemia (endothelium-dependent vasodilation), and local heating to 42 °C. Lipid profile was similar in both groups. Resting heart rate was significantly lower in windsurfers. Baseline cutaneous vascular conductance (CVC) values were similar in both groups (0.059 ± 0.016 and 0.051 ± 0.009). During reactive hyperaemia, normalized peak CVC value was significantly higher in the windsurfers group (1775.4 ± 286.9 and 826.4 ± 121.7 % baseline CVC; p = 0.01). Normalized peak CVC value in response to local heating (42 °C) was not significantly different between both groups (2359.4 ± 346.1 and 1467.7 ± 282.6 % baseline CVC). Endothelium-dependent vasodilation in cutaneous microcirculation is significantly enhanced in the forearm skin of highly trained windsurfers when compared to sedentary controls.